MULTICULTURAL CLASSROOMSIN TEACHING: FOSTERING EQUITYAND CULTURAL COMPETENCE - valent raynaldi (UPT Perpustakaan Universitas Jambi, 2025)
This paper explores the key concepts, strategies, and challenges associated with teaching in multicultural classrooms. This article examines issues involved in teaching culturally diverse students and questions current practice in multicultural teacher education. Alternative approach to preparing teachers for multicultural classrooms. It highlights the importance of culturally responsive teaching, differentiated instruction, and promoting intercultural competence as essential strategies for engaging students from diverse backgrounds. The challenges in implementing multicultural education—such as language barriers, implicit bias, curriculum gaps, and socio-economic disparities—are also addressed. Recent research underscores the necessity of professional development for educators and systemic changes in curriculum design to better reflect cultural diversity. Through an analysis of the current landscape of multicultural education, the paper emphasizes the need for a comprehensive approach that incorporates diverse perspectives in teaching practices and institutional policies. By overcoming these challenges, educators can create learning environments where all students, regardless of background, can achieve their full potential. The conclusion underscores the importance of continuous learning, adaptability, and inclusive pedagogies in shaping the future of multicultural education.